Inhibition of Horse Liver Alcohol Dehydrogenase by Methyltin Compounds - Pavel V. Bychkov; Tatyana N. Shekhovtsova; Elena R. Milaeva (Bioinorganic Chemistry and Applications)
The study of inorganic tin (SnCl2, SnCl4) and methyltin compounds (MeSnCl3, Me2SnCI2, Me3SnCl) effects on the enzymatic activity of alcohol dehydrogenase (ADH) in the reaction of ethanol oxidation has been carried out. The experimental results of the study show that inorganic tin and methyltin substances induce slight inhibition of the catalytic activity of horse liver alcohol dehydrogenase (HLADH), unable to be improved during pre-incubation with the enzyme. The conditions for carrying out the kinetic investigation of the mentioned phenomenon were optimized and as it turned out the mechanism of methyltin trichloride action, as the most effective methyltin inhibitor, is more complex than the proposed interaction of the metal atom with SH-groups of the enzyme protein. It was demonstrated that the tin compounds act in the same manner as methylmercury compounds and might serve as oxidative agents towards the co-enzyme NADH. Kinetic data on MeSnCl3 were calculated. Data acquired on NAD-dependent ADH from horse liver and those regarding NAD-dependent LDH from sturgeon liver were compared.